On the production of knowledge fieldwork in South Gujarat, 1971 - 1991 - Streefkerk, Hein (Comparative Asian Studies, 1993)
The researcher as research instrument is a major feature of socio-anthropological fieldwork. The gathering of data, their analysis, and evaluation are highly sensitive to the personality, perception and theories of the fieldworker. It causes divergent representations and valuations of the same processes and phenomena by different researchers, or different interpretations of the same subject by the same fieldworker over the years